2017
DOI: 10.22159/ajpcr.2017.v10i4.16932
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Microbial Flora for Infertility Couples in an Indian Tertiary Care Teaching Hospital

Abstract: Objective: Infertility has been known to cause serious social and emotional problems in India. Microorganisms may be a primary cause for this infertility. This study was carried out to know the prevalence of microorganisms in the infertility couples of a tertiary caring teaching hospital. Methods:One thousands of couples were screened for the infertility test presented at the outpatient Department of Obstetrics and Gynaecology.The suspected infertility couples were tested for microbial contamination in their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…An Indian study by Mishra et al [ 26 ] included 288 infertile couples, performing either cervical or high vaginal swab and semen samples for culture analyses. A high prevalence of Escherichia coli was implicated in primary infertility, even though it was not the only isolated pathogen; hence, the authors suggested adopting therapeutic managements strategies of couples with primary infertility such as antibiotics and a parallel treatment to avoid cross-retransmission.…”
Section: Discussionmentioning
confidence: 99%
“…An Indian study by Mishra et al [ 26 ] included 288 infertile couples, performing either cervical or high vaginal swab and semen samples for culture analyses. A high prevalence of Escherichia coli was implicated in primary infertility, even though it was not the only isolated pathogen; hence, the authors suggested adopting therapeutic managements strategies of couples with primary infertility such as antibiotics and a parallel treatment to avoid cross-retransmission.…”
Section: Discussionmentioning
confidence: 99%
“…Around one in six or seven couples may have difficulty getting pregnant. Unexplained infertility in addition to common causes of infertility such as ovulation problems, tubal blockage, male associated infertility, uterine problems, and infections are causes which could eventually lead to using associated reproductive technology commonly known as ART in the treatment of infertility [3][4][5][6]. In vitro fertilization (IVF) as a helpful way to treat infertility, particularly fallopian tube and ovarian-related infertility, may lead to failure due to many factors such as female age, embryo quality, ovarian response, or implantation issues.…”
Section: Introductionmentioning
confidence: 99%